Characterization of Rambutan Cultivars (Nephelium lappaceum) Based on Leaf Morphological and Genetic Markers - Manggabarani, Andi Madihah; Chikmawati, Tatik; Hartana, Alex (Biosaintifika: Journal of Biology & Biology Education, 2018)
Rambutan (Nephelium lappaceum) is an economically important plant which is native to Indonesia and Malaysia. The diversity of rambutan in Indonesia is abundance especially in Kalimantan where the wild relatives still grow naturally. Rambutan cultivars are usually differed from each other based on fruit morphological characters. However, rambutan tree begins to fruiting for the first time in 3-4 years. Therefore, another character is needed to characterize each cultivar in a short period. The objectives of this study were to distinguish rambutan cultivars using leaf morphological and Inter-Simple Sequence Repeat (ISSR). As many as 30 rambutan cultivars collected from Cipaku Orchard and Mekar Sari Park were observed for their morphological and ISSR characters. Six characters of were surveyed for leaf morphological character. For the genetic character, 6 out of 31 ISSR primers were assessed which resulted in 58 polymorphic bands (87%). As a result, leaf morphological characters overlapped among cultivars causing difficulties distinguishing each cultivar. ISSR marker, three major clusters have been identified according to UPGMA method. Index similarity among rambutan accessions from ISSR data ranged from 48-93%. As a conclusion, ISSR marker could be potentially applied rambutan cultivars characterization.